Komi Latin Letters, Degrees of UNICODE Facilitation - Rueter, Jack; Ponomareva, Larisa (2025)
The Komi-Permyak and Komi-Zyrian language forms are two writing traditions of the pluricentric Komi language, whose first debut in as a literary medium stems from the 14th Century. The alphabets and writing systems have changed numerous times over the centuries, and most published media in the two languages are facilitated by UNICODE. Thereis, however, one specific time period, where the digital accessibility of plentiful publications is hampered by missing representation in UNICODE, and that is the time span 1932–1938; the Komi languages were printed in a Latin script with numerous and special Latin letters. Due to the poor quality of typography in this era, the characters have been determined transitional, and therefore it has been suggested that characters existing in UNICODE, regardless of range, might be used to alleviate the issue of missing representation. Bearing this in mind, the number of required letters dropped from an original estimation of 18 to 8 or perhaps simply combining descenders. ”UNICODE Script Ad Hoc” has provided helpful suggestions for providing digital means for the Komi languages, and with UNICODE in place, the next hurdle will be dealing with font issues. Peer reviewed